2004
DOI: 10.1021/bi049887s
|View full text |Cite
|
Sign up to set email alerts
|

Translational Control of Apolipoprotein B mRNA:  Regulation via Cis Elements in the 5‘ and 3‘ Untranslated Regions

Abstract: Translational control of apolipoprotein B (apoB) mRNA has been previously documented; however, the molecular mechanisms that govern translation of apoB mRNA are unknown. We investigated the role of the untranslated regions (UTR) in the regulation of apoB mRNA translation first by analyzing apoB UTR sequences using M-fold, a program used to predict RNA secondary structure. M-fold analysis revealed hairpin-like elements within the 5'UTR and 3'UTR of apoB mRNA with potential to form stable secondary structure. Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…Insulin action on apo B appears to involve not only the activation of PI3-kinase, but also the localization of PI3-kinase near the site of apo B synthesis (23). Mechanisms involved in the synthetic effect have not been established but may involve more efficient apo B translation (1,25). It is not known how fluctuations in PI3-kinase activity in vivo adjust hepatic VLDL apo B output.…”
mentioning
confidence: 99%
“…Insulin action on apo B appears to involve not only the activation of PI3-kinase, but also the localization of PI3-kinase near the site of apo B synthesis (23). Mechanisms involved in the synthetic effect have not been established but may involve more efficient apo B translation (1,25). It is not known how fluctuations in PI3-kinase activity in vivo adjust hepatic VLDL apo B output.…”
mentioning
confidence: 99%
“…It was revealed that ApoB was regulated at multiple levels, such as gene transcription and the 5'UTR and 3'UTR of ApoB mRNA were likely to regulate ApoB mRNA translation and protein synthesis (Pontrelli et al 2004). Meanwhile, miRNAs are proved to repress the translation of transcripts by degrading their target mRNA transcripts through binding to the 3'UTR (Bartel 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on the regulatory role of ApoB mRNA untranslated region (UTR) suggested that both 5'UTR and 3'UTR are likely to govern ApoB mRNA translation and protein synthesis (Pontrelli et al 2004); other studies revealed that the ApoB was regulated at multiple levels, including gene transcription, mRNA editing, protein translation and translocation into the endoplasmic ergatoplasm and intracellular degradation of nascent proteins (Wang et al 2003). However, the possible role of microRNAs (miRNA) in regulating ApoB expression remains unknown yet.…”
mentioning
confidence: 99%
“…Second, these repeats are present in the 3' untranslated region and do not play any role in the apoB protein sequence. VNTR may be in linkage disequilibrium with other polymorphisms in the same gene or other nearby genes to develop lipid alterations (Pontrelli et al, 2004). Friedl et al (1990) reported that the apoB 3' VNTR shows strong linkage disequilibrium with a polymorphic EcoRI site in exon 29, which might contribute, in part, to the elevated levels of serum cholesterol and apoB in L carriers.…”
Section: Discussionmentioning
confidence: 99%